2013
DOI: 10.1371/journal.pone.0068865
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Acclimation Capacities to Ocean Warming and Acidification Are Limited in the Antarctic Nototheniid Fish, Notothenia rossii and Lepidonotothen squamifrons

Abstract: Antarctic notothenioid fish are characterized by their evolutionary adaptation to the cold, thermostable Southern Ocean, which is associated with unique physiological adaptations to withstand the cold and reduce energetic requirements but also entails limited compensation capacities to environmental change. This study compares the capacities of mitochondrial acclimation to ocean warming and acidification between the Antarctic nototheniid Notothenia rossii and the sub-Antarctic Lepidonotothen squamifrons, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 69 publications
9
72
1
Order By: Relevance
“…Our observed decline in heart and brain mitochondrial capacity supports the prediction of decreased mitochondrial capacity at high temperatures (Figs 2-7). Similar declines in mitochondrial function have been observed previously in heart and liver mitochondria in F. heteroclitus (Baris et al, 2016a;Chung and Schulte, 2015) and in other ectotherms (Khan et al, 2014;Guderley and Johnston, 1996;Strobel et al, 2013). Acclimation to 33°C results in a decline in routine oxygen consumption in F. heteroclitus, suggesting that this temperature causes a collapse of aerobic metabolism or that active metabolic suppression is taking place (Healy and Schulte, 2012).…”
Section: Does Acclimation To 33°c Results In a Suppression Of Mitochonsupporting
confidence: 79%
See 1 more Smart Citation
“…Our observed decline in heart and brain mitochondrial capacity supports the prediction of decreased mitochondrial capacity at high temperatures (Figs 2-7). Similar declines in mitochondrial function have been observed previously in heart and liver mitochondria in F. heteroclitus (Baris et al, 2016a;Chung and Schulte, 2015) and in other ectotherms (Khan et al, 2014;Guderley and Johnston, 1996;Strobel et al, 2013). Acclimation to 33°C results in a decline in routine oxygen consumption in F. heteroclitus, suggesting that this temperature causes a collapse of aerobic metabolism or that active metabolic suppression is taking place (Healy and Schulte, 2012).…”
Section: Does Acclimation To 33°c Results In a Suppression Of Mitochonsupporting
confidence: 79%
“…Low-temperature acclimation is associated with increased mitochondrial oxidative phosphorylation (OXPHOS) capacity, mitochondrial volume density and alterations in mitochondrial membrane composition (Chung and Schulte, 2015;Egginton and Johnston, 1984;Grim et al, 2010;Fangue et al, 2009;Kraffe et al, 2007;Dhillon and Schulte, 2011;Schnell and Seebacher, 2008). In contrast, hightemperature acclimation has been associated with changes in mitochondrial membrane fatty acid saturation and lowered mitochondrial respiratory capacity (Chung and Schulte, 2015;Guderley and Johnston, 1996;Khan et al, 2014;Strobel et al, 2013;Baris et al, 2016a;Fangue et al, 2009). These changes may induce trade-offs causing mitochondrial function to decline at temperatures that were not previously harmful, which may account for shifts in whole-animal thermal tolerance following acclimation (Fangue et al, 2009;Chung and Schulte, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, suppression of metabolism with acclimation to high temperature could be interpreted as a benefit of acclimation. Although there are relatively few studies examining this phenomenon, some groups have demonstrated that high-temperature acclimation results in a decrease in mitochondrial membrane fatty acid saturation and a decrease in respiration rate (Guderley and Johnston, 1996;Khan et al, 2014;Strobel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite projections that indicate changes in SST and partial pressure of CO 2 (Ṗ CO2 ) in seawater will impact higher latitudes faster and to a greater Is warmer better? Decreased oxidative damage in notothenioid fish after long-term acclimation to multiple stressors Laura A. Enzor and Sean P. Place* extent than temperate regions (Walther et al, 2002;Orr et al, 2005;Turner et al, 2005;McNeil and Matear, 2008;Fabry et al, 2008;Fabry et al, 2009;Halpern et al, 2008;McNeil et al, 2010;Mathis et al, 2011a;Mathis et al, 2011b), only a handful of studies have examined the effects of ecologically relevant increases in seawater Ṗ CO 2 on high latitude marine teleosts (Hurst et al, 2012;Strobel et al, 2012;Enzor et al, 2013;Strobel et al, 2013a;Strobel et al, 2013b). Similar to impacts seen with elevated temperature, ocean acidification may also perturb oxidative stress in marine teleosts (Murphy, 2009;Tomanek et al, 2011) and may even exacerbate the detrimental effects of reactive oxygen species at the cellular level (Ezraty et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the potential synergistic effects of increased temperature and increased Ṗ CO 2 in fish have only been examined in a small number of studies (Pankhurst and Munday, 2011;Nowicki et al, 2012;Strobel et al, 2012;Enzor et al, 2013;Strobel et al, 2013a;Strobel et al, 2013b;Gräns et al, 2014). We have previously shown that increased temperature and Ṗ CO 2 levels result in a rapid increase in resting metabolic rates in several species of Antarctic fish (Enzor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%